KONTROL DIRI TERHADAP PENGAMBILAN KEPUTUSAN KARIER SISWA (Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study aims to determine the level of self-control that influences students' career decision-making. Adolescents who have low self-control tendencies will make career decisions without considering the consequences and responsibilities they have to endure. The subjects of this study were seven junior high school students with an age range of 14–15 years. Data collection techniques in this study used direct observation and interview techniques. The results of this study showed that the students who were interviewed said they made career decisions of their own free will, but some of them were due to their parents, and some made decisions after considering their family circumstances. Based on the results of research on self-control in students' career decision-making, it was found that the contribution of self-control to decision-making abilities was still quite low but had a positive direction. so that the higher the student's self-control, the more influential he is in his decision-making. Keywords: self-control, adolescents, and adolescent behavior.